Faktor-faktor yang Dipertimbangkan Konsumen dalam Keputusan Pembelian Produk Endek di Kota Denpasar - Waskiarani, L.G. Indhira; Sulistyawati, Eka (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
ABSTRACT The purpose of this study was to determine the factors that consumers consider the product purchase decisions endek in Denpasar and to determine which variables representing each factor that consumers consider the product purchase decisions endek in Denpasar. This study of 100 respondents using purposive sampling technique. Based on the research results can be that the promotion factors, product factors, collection factors, and friends factors into consideration in purchasing decisions of consumers endek products in Denpasar and variables representing each factor that consumers consider the product purchase decisions endek in Denpasar is the promotion variable, products variable, a collection of variables, and friends variable. Key words : factors , consumer behavior , decision purchase Normal 0 false false false EN-US X-NONE X-NONE